2020
DOI: 10.3390/molecules25194467
|View full text |Cite
|
Sign up to set email alerts
|

EGF Conjugation Improves Safety and Uptake Efficacy of Titanium Dioxide Nanoparticles

Abstract: Titanium dioxide nanoparticles (TiO2 NPs) have a strong potential for cancer therapeutic and bioimaging applications such as photodynamic therapy (PDT) and photodynamic diagnosis (PDD). Our previous results have shown that TiO2 NPs have a low cellular uptake and can induce cell proliferation. This suggests that TiO2 NPs could increase the risk of tumor overgrowth while being used for PDD and PDT. To solve this problem, we constructed epidermal growth factor-ligated polyethylene glycol-coated TiO2 NPs (EGF-TiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In another study, Salama et al investigated the attachment of the epidermal growth factor receptor (EGFR) on PEG-modified TiO 2 NPs for increasing the PDT effect for epithelial cell carcinoma (A431 cell line). 150 The EGFR is vital for cell proliferation and it is highly expressed on many cancer cells, so for this reason, the modification of TiO 2 NPs with EGF could increase the efficiency and selectivity of TiO 2 -based PDT. Their results showed that the EGF modification of TiO 2 NPs–PEG diminished the cell viability of the cancer cells via interrupting DNA synthesis.…”
Section: Biological Applications Of Modified Tio2npsmentioning
confidence: 99%
“…In another study, Salama et al investigated the attachment of the epidermal growth factor receptor (EGFR) on PEG-modified TiO 2 NPs for increasing the PDT effect for epithelial cell carcinoma (A431 cell line). 150 The EGFR is vital for cell proliferation and it is highly expressed on many cancer cells, so for this reason, the modification of TiO 2 NPs with EGF could increase the efficiency and selectivity of TiO 2 -based PDT. Their results showed that the EGF modification of TiO 2 NPs–PEG diminished the cell viability of the cancer cells via interrupting DNA synthesis.…”
Section: Biological Applications Of Modified Tio2npsmentioning
confidence: 99%